2021
DOI: 10.1108/ijtc-10-2020-0219
|View full text |Cite
|
Sign up to set email alerts
|

The effective responses of a tourism and gaming city towards the devastating effects of pandemic: a case study of Macao

Abstract: Purpose COVID-19 has hard-hit the global economy when the majority of developed countries could not demonstrate effective resolutions even a year after the outbreak. This study aims to present how government or policymakers could minimize the negative impacts of major incidents (pandemic) and speed up the process of recovery. It was also intended to identify effective strategies for crisis management. Design/methodology/approach A mixed research method was applied. Qualitative research studies of interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Though many scholars have emphasized the prominence of government and business collaborations in managing the COVID-19 crisis (e.g. Im et al, 2021;Koh, 2020), few have examined the operational business mechanisms underpinning such initiatives (e.g. Usher et al, 2020).…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…Though many scholars have emphasized the prominence of government and business collaborations in managing the COVID-19 crisis (e.g. Im et al, 2021;Koh, 2020), few have examined the operational business mechanisms underpinning such initiatives (e.g. Usher et al, 2020).…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…Some papers provide arguments and evidence in favour of the application of CSR by tourism firms to address the Covid-19 crisis. Among them, Im et al (2021) found that the tourism destination Macao benefited from the initiatives of local large enterprises inspired by the government and informed by CSR (such as, for example, avoiding laying off their employees). Another study reported that hospitality companies listed on Chinese stock exchanges registered positive reactions from stakeholders within five days of press releases presenting companies' CSR activities related to Covid-19 ( Qiu et al, 2021 ).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…Despite China’s remarkable achievements in urban tourism over the past four decades (Bao, Li, & Liang, 2020), the COVID-19 pandemic has severely impacted the global tourism industry, with China being no exception. The number of tourists and revenue generated by the tourism industry have both been significantly threatened, and tourist behavior has changed as a result (Im, Lam, & Ma, 2021; Wang, Tian, Filimonau, Ning, & Yang, 2022). As a result, the recovery of urban tourism has become an urgent issue (Anguera-Torrell, Vives-Perez, & Pedro Aznar-Alarcon, 2021).…”
Section: Introductionmentioning
confidence: 99%